Sustainable Lean Manufacturing Integration in New Product Development to Mass Production - Cheng Chee Hooi, Suzari Abdul Rahim (International Journal of Advanced Science and Technology, 2020)
New product development is crucial to manufacturing firm in getting new develop product that is manufacturable in mass manufacturing to fulfil the fast pace of customer in highly competitive semiconductor market. Lean manufacturing on the other hand is core principle of practice to eliminate waste in process flow and create value to the customer. However, the linking new product development and implementation of lean manufacturing in this phase is still offer plenty of opportunities for improvement. The research aims to address the gap of lean manufacturing practice and sustainability for new product development that will transition into ramp phase to meet customer demand. Many aspects had been researched and imply to ensure the new context of new product development able to achieve flawless operation with the adopting of lean manufacturing influence. The outcome of the research will seek methods will supporting to new product development incorporate lean manufacturing to perform more efficient in current fast-moving market where lifecycle of product is short due to new product keep entering market and prices are eroding at faster than before. The research will be able to strengthen lean implementation in development phase and offer approach to effective cost saving at the very start of the product life cycle with the use of waste reduction in lean manufacturing theory.